The Feed the Future Nigeria agricultural policy project - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Successful implementation of any government policy requires credible evidence in monitoring progress and revising approaches as priorities shift with changing policy concerns on emerging issues. This means having sufficient capacity to conduct policy analysis and research to fill key knowledge gaps. It also requires a demand for such research (by policy makers) to inform the national policy process and to improve the design, implementation, monitoring, and evaluation of the policies. Nigerian agriculture policymaking has evolved and the capacity to make and implement policy has improved over time. However, shortfalls in human and institutional capacity remain which limit the potential to support the efforts of the Federal Ministry of Agriculture and Rural Development (FMARD) in implementing their policies and programs. The Nigeria Agriculture Policy Project is designed to address this need for policy research and capacity building, and to ensure that Nigerian institutions are equipped to respond effectively and in a timely manner to the increasing capacity, knowledge and information needs of FMARD. The Feed the Future Nigeria Agricultural Policy Project is a five year, $12.5 million initiative. It is a joint effort between Michigan State University (MSU) and the International Food Policy Research Institute (IFPRI)’s Nigeria Strategy Support Program (NSSP) funded by USAID-Nigeria.